ALAT BANTU MOBILITAS TUNANETRA BERBASIS MICROCONTROLLER ARDUINO - Nurul Listi Komah; Rizki Wiradika; I Made Andik Setiawan; Aan Febriansyah (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
Not everyone has a normal eye condition, there are some people who have vision problems from birth, and some are caused by the person having an accident. To help with these problems, it is possible to design a tool for visually impaired people based on arduino nano that can facilitate the visually impaired to carry out daily activities. This tool will provide information in the form of distance of an obstacle in the form of sound and user location information, hc-SR04 ultrasonic sensor is used to detect obstacles or obstacles that provide sound output in the form of buzzers. As for location data using the 6m neo ublox gps module sent using the gsm sim 800l module.